2017
DOI: 10.4995/wrs.2017.5216
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance and body reserves in rabbit females selected for longevity

Abstract: The aim of this study was to compare the energy balance and dynamic of body reserves in rabbit females divergently selected for longevity. One hundred and twenty-nine females from a high longevity line (HL) and 131 females of a low longevity line (LL) were studied from the 1 st to the 3 rd kindling. ). The total body electric conductivity (TOBEC) method was used to estimate the body reserves in all females at artificial insemination and at weaning, and at kindling in females that achieved parturition. Energy b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…From 6th parity and 7th AI on, fertility began to decrease, first to 77%, then in the 8th AI to 75%, in the 9th AI to 73%, and so on. Garreau et al [ 69 ] observed a decrease in kindling rate, from 0.78 in the first AI to 0.69 in first parity and second AI and 0.73 in 3rd AI. With regard to age, in a more recent database of 43,803 does examined on 270 rabbitries between 2006 and 2019, the median was five parities (minimum to maximum: 1–39) and the mean, six (results not presented).…”
Section: Resultsmentioning
confidence: 99%
“…From 6th parity and 7th AI on, fertility began to decrease, first to 77%, then in the 8th AI to 75%, in the 9th AI to 73%, and so on. Garreau et al [ 69 ] observed a decrease in kindling rate, from 0.78 in the first AI to 0.69 in first parity and second AI and 0.73 in 3rd AI. With regard to age, in a more recent database of 43,803 does examined on 270 rabbitries between 2006 and 2019, the median was five parities (minimum to maximum: 1–39) and the mean, six (results not presented).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, reproductive performance was similar between lines at the 2 nd generation (Garreau et al, 2017). In this experiment, the high longevity line accreted more body reserves at the onset of reproductive life than the low line and thereafter maintained higher body reserves until third delivery.…”
Section: Selection Programmes and Response To Selectionmentioning
confidence: 58%
“…Based on current rabbit breeding programmes, the reproduction rhythm of the rabbit does is generally 42 d, which means that rabbit does spend their productive life either gestating, lactating or both. Females have to simultaneously allocate their resources to maintenance and to milk production, as well as to the developing foetuses (Garreau et al, 2017). This production system is very demanding, and consequently the annual replacement rate in rabbit does is very high (120%) Matics et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…This production system is very demanding, and consequently the annual replacement rate in rabbit does is very high (120%) Matics et al (2014). The main causes for doe replacement are health problems, poor prolificacy or fertility and poor body condition (Garreau et al, 2017). Body condition is related to the energy balance of the does, which is positive during the first 3 wk of gestation and results in increased fat reserves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation